Religiosidade de pacientes evangélicos nas percepções de psicólogos em contextos hospitalar e em CAPS - Ruas, Evelyn Figueira Lima (2018)
Given the cultural and religious diversity that characterizes Brazil and the growing number of Protestants and Evangelicals in the country, it is relevant to know how this religious modality has impacted health contexts, especially in the experience of psychologists who work in hospital and mental health contexts. This work intends to contribute in this direction, and it aimed to investigate the perceptions of psychologists who work in CAPS and in hospital setting, in the Federal District, on the Protestant and Evangelical religiosity of patient/users (and/or their companions) as the way they refer to dealing with such religious manifestations within the scope of their care. The study was based on Husserlian phenomenology. The methodology has been inspired by phenomenology and the empirical-phenomenological descriptive method proposed by Amedeu Giorgi was used in the phenomenological analysis of interviews with seven psychologists who work in CAPS and eight who work in a hospital context. These interviews were recorded and transcribed. After that, they have been exhaustively and sorely analyzed, in order to access the interviewees lived experience in relation to the studied phenomenon and to understand it in a contextualized way, seeking to learn the meaning of each reported experience , without losing sight of the meaning of the whole, according to the experiences which have been shared. The results show how much the Protestant and Evangelical religiosity are present in the two contexts of psychologists' performance, manifesting themselves both by CAPS users and hospital inpatient services, as well as by their families and by the health professionals themselves. The professionals shared the implications, both propulsive and cross-over to their work of health care, of this religiosity in both contexts of action, with a predominance of the sense it gives to life and suffering of the people, helping in the health-disease processes, but also of the obstacle to the promotion of health that this religiosity poses, through doctrines and dogmas, sometimes strict and oppressive. They were unanimous in affirming their tendency to seek to respect and accept such religious manifestations, but they also shared their difficulties in dealing with them, mainly due to their failure to approach the theme throughout their professional training. It is necessary to carry out studies aimed at understanding the trajectories of the theoretical and religious formation of psychologists in their professional practice in the contexts of action mentioned.